A model of the origins and development of Aleut - Anna Berge; Ben Potter; Jason Rogers (Quaternary Environments and Humans)
It has long been thought that Unangam Tunuu (Aleut) must have undergone substantial language contact at some point, given its divergent lexicon, features seemingly shared with Dene languages, and a single feature shared with Eyak, Tlingit, and Haida. To date, however, the nature of prehistoric language contact event(s) has remained unclear. Collaboration between the authors has resulted in a cohesive model of language contact mechanisms, together with the timing and geographical location of these contacts, allowing us to make sense of previously unexplained developments in the history and prehistory of Unangam Tunuu. We here develop an integrated archaeogenetic model consistent with existing data on archaeological and genetic patterning among northern populations to evaluate the prehistoric development of Unangam Tunuu and related languages. Climate impacts and extreme events (e.g., volcanism) have influenced these populations. We posit admixture of Proto-Aleut with Proto-Dene speakers in southwest Alaska (Lower Kuskokwim basin) between ∼4800–3700 years ago, followed by admixture with Late Anangula and Ocean Bay 2 populations in the Alaska Peninsula/Aleutian Islands and southcentral Alaska respectively between ∼4000–3700 years ago. This contact and admixture altered the language of Proto-Aleut populations compared to their Proto-Inuit/Yupik relatives to the north. Proto-Aleut populations had a large geographic distribution, encompassing the Alaska Peninsula, Kodiak Island, and the Kenai Peninsula until ∼1000–800 years ago, when they were replaced or assimilated by southern expansions of Yupik speakers associated with the Koniag tradition.